Can we use psychoactive drugs to treat pruritus?. Issue 12 (6th June 2019) - Reszke, Radomir; Szepietowski, Jacek C.
Abstract: Pruritus is a frequent complaint both in dermatology and general medicine. This burdensome symptom has a complex and multifactorial pathogenesis, with the key involvement of central nervous system in its development. Psychoactive drugs (psychopharmaceuticals) encompass several therapeutic groups utilized mainly in psychiatry. However, these drugs are occasionally used in dermatological practice and may contribute to alleviation of pruritus in a variety of cutaneous and extracutaneous disorders. This review article summarizes the role of H1‐antihistamines, antidepressants, antipsychotics and antiepileptics in managing pruritus.